2018
DOI: 10.9744/jak.20.1.39-52
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Knowledge Management, Organization Culture, and Innovation with Organizational Performance: A Case at Study Institute Research XYZ

Abstract: The purpose of this study is to analyze the impact of innovation as the mediation variable towards the knowledge management relationship and also culture organization towards organization performance. The population in this study are employees of XYZ. The data collection in this study is conducted by using the questionnaire and then the data is analyzed with Partial Least Squares method. The results show that; (1) knowledge management has the influence on innovation; (2) The effect on the organizational cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…This finding contradicts the findings of (AL-Hakim et al, 2012;Byukusenge et al, 2016;Wibowo et al, 2021;Eugenie et al, 2017), that highlighted business performance won't be impacted by knowledge management except it goes through intervention. However, it's similar to the recent findings of (Ullah et al, 2019;Davila et al, 2019;Puryantini, 2018) in which knowledge management had a direct influence on organizational performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding contradicts the findings of (AL-Hakim et al, 2012;Byukusenge et al, 2016;Wibowo et al, 2021;Eugenie et al, 2017), that highlighted business performance won't be impacted by knowledge management except it goes through intervention. However, it's similar to the recent findings of (Ullah et al, 2019;Davila et al, 2019;Puryantini, 2018) in which knowledge management had a direct influence on organizational performance.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Nawab et al (2015) also revealed that knowledge management processes have an indirect significant impact on business performance through innovation in the banking industry, whereas Alrubaiee et al (2015), Byukusenge et al, (2016) Yousif Al-Hakim, et al, (2013) revealed a full mediation of innovation between knowledge management and organizational performance of different sectors. However, in the study of Puryantini (2018), knowledge management had no indirect effect on business performance. Even though innovation has a direct impact on firm performance, it was considered a mediating variable in the knowledge management framework in the above literature, with only Lee et al, (2010) exploring the joint impact of knowledge management and marketing innovation strategy on market performance.…”
Section: Knowledge Management Marketing Innovation and Firm Performancementioning
confidence: 74%
See 1 more Smart Citation
“…Investigar a relação entre cultura organizacional, estilo de liderança, aprendizagem organizacional e inovação organizacional foi o objetivo da pesquisa de Tang e Yeh (2015), que chegaram à conclusão que o estilo de liderança não tem impacto direto na capacidade de inovação. Analisar o impacto da inovação como variável de mediação para a relação de GC e da cultura organizacional para o desempenho da empresa foi o objetivo estabelecido por Puryantini, Rofikotul, Tjahjadi, et al (2018) ao desenvolverem seu estudo num instituto de pesquisas da Indonésia. Os autores destacam que a cultura organizacional pode afetar a inovação, seja para encorajá-la ou inibi-la.…”
Section: Resultados Pesquisa Bibliográficaunclassified